ChemInform Abstract: Diastereoselective Synthesis of β‐Heteroaryl syn‐α‐Methyl‐β‐amino Acid Derivatives via a Double Chiral Auxiliary Approach. Issue 26 (6th June 2013) - Bian, Jianwei; Blakemore, David; Warmus, Joseph S.; Sun, Jianmin; Corbett, Matthew; Rose, Colin R.; Bechle, Bruce M.
Abstract The addition of chiral auxiliary (II) to heterocyclic tert‐butyl sulfinimines (I) proceeds with high diastereoselectivity (92—98% d.e.